The detection of macroprolactin by precipitation and ultrafiltration methods - Beda-Maluga, Karolina; Pisarek, Hanna; Komorowski, Jan; Pawlikowski, Marek; Świętosławski, Jacek; Winczyk, Katarzyna (Endokrynologia Polska, 2011)
Prolactin (PRL) exists in human blood in several molecular forms. Macroprolactin (MaPRL), which most often consists of monomeric PRL and immunoglobulin G, has the highest molecular weight but no biological activity. Immunoassays do not distinguish MaPRL from monomeric PRL, what can lead to an incorrect diagnosis of hyperprolactinaemia. The most commonly used technique to separate the isoforms of PRL is precipitation with polyethylene glycol (PEG). Another technique - ultrafiltration - seems to be useful in MaPRL detection. The aim of this study was to evaluate the occurrence of MaPRL in hyperprolactinaemic patients and to compare the results obtained by precipitation and ultrafiltration. The study was conducted on 120 sera obtained from patients hospitalised in the Department of Clinical Endocrinology, Medical University of Lodz, in whom PRL concentration was above 30 ng/mL Of these 120 patients, 25 had pituitary adenoma, 52 had polycystic ovary syndrome (PCOS), and 43 had idiopathic hyperprolactinaemia (HPRL). Macroprolactin was detected using two methods: precipitation with PEG and ultrafiltration. Concentration of PRL was measured by Immulite 1000 immunoassay (Siemens). We detected a predominance of MaPRL in ten patients (three with macroprolactinoma, three with PCOS and four with HPRL) using precipitation and ultrafiltration. Positive correlation and diagnostic concordance between the results of precipitation and ultrafiltration were noted, especially in the group with functional hyperprolactinaemia. In half of the patients with macroprolactinaemia, and in 12 of the 110 subjects without significant amounts of MaPRL, real PRL concentration was within the reference range. MaPRL is not a significant clinical problem in the studied population. However, in patients with hyperprolactinaemia, especially non-organic, screening for macroprolactinaemia should be performed. The effectiveness of the precipitation and ultrafiltration methods for detecting MaPRL is comparable in functional hyperprolactinaemia, but the usefulness of ultrafiltration in patients with pituitary adenoma requires further examination.